PENGARUH KONSELING KESEHATAN TERHADAP KEPATUHAN IBU POST PARTUM DALAM MEMBERIKAN KOLOSTRUM PADA BAYI BARU LAHIR DIRUANG BERSALIN RS - Uni Wulandari; Herry Susanto; Kurnia Wijayanti (Journal Healthcare Education, 2026)
Colostrum is an important component of breast milk, a yellowish fluid that is secreted in the first few days after delivery. Colostrum is rich in antibodies that play a role in the formation of the immune system and the maturation of the baby's organs. Objective: This study aims to determine the effect of health counseling on postpartum mothers' compliance in providing colostrum to newborns in the Delivery Room of Sari Asih Hospital, Serang. Method: Quantitative research with a quasi-experimental post-test only control group design involving 2 groups, namely the intervention group and the control group with 43 respondents in each group. The research instrument used a colostrum compliance questionnaire. Data analysis was carried out using the chi-square statistical test. Results: The results of univariate analysis showed that the majority of postpartum mothers in the intervention group were compliant in providing colostrum (55.8%), and the majority of postpartum mothers in the control group were not compliant in providing colostrum (62.8%). The results of bivariate analysis showed that there was a difference in compliance in providing colostrum, where postpartum mothers in the intervention group were more compliant than postpartum mothers in the control group with a p value of 0.023. Conclusion: Postpartum mothers who received counseling and leaflets had higher compliance compared to postpartum mothers who received only leaflets.